2014
DOI: 10.1186/1472-6882-14-418
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of early liver fibrosis by herbal compound “Diwu Yanggan” through modulating the balance between epithelial-to-mesenchymal transition and mesenchymal-to-epithelial transition

Abstract: BackgroundDiwu Yanggan (DWYG) is a Chinese compound herbal preparation which consists of five Chinese herbs. This study investigates the preventative effects of DWYG on liver fibrosis induced by carbon tetrachloride (CCl4) and explores its possible mechanisms of action.MethodsLiver fibrosis was induced in male Wistar rats by injecting a 50% CCl4/soybean oil solution subcutaneously twice a week for six weeks. After six weeks of treatment, serum aspartate transaminase (AST) and alanine transaminase (ALT) assay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…In agreement with previous studies, our results showed that liver fibrosis induced by CCl 4 is associated with excessive activation of Hh signalling as shown by increased expression of the Hh pathway components, Ptch‐1, Smo and the transcriptional activator Gli‐2, where the level of Hh pathway activation paralleled the increase in hepatic collagen content (Fleig et al , ; Choi et al , ; Shen et al , ). Activation of the Hh pathway results in Smo‐dependent inhibition of PKA.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous studies, our results showed that liver fibrosis induced by CCl 4 is associated with excessive activation of Hh signalling as shown by increased expression of the Hh pathway components, Ptch‐1, Smo and the transcriptional activator Gli‐2, where the level of Hh pathway activation paralleled the increase in hepatic collagen content (Fleig et al , ; Choi et al , ; Shen et al , ). Activation of the Hh pathway results in Smo‐dependent inhibition of PKA.…”
Section: Discussionsupporting
confidence: 93%
“…First, it will distort the hepatic architecture and vasculature; second, it will have a deleterious effect on hepatic function; and third, it will increase the propensity for neoplastic transformation. Many studies have showed that liver fibrosis could be reversed, for example, by administering antiviral treatment for chronic viral hepatitis 4,5 . In addition, the severity of liver fibrosis affects the prognosis of liver cancer surgery.…”
Section: Introductionmentioning
confidence: 99%
“…TGF-b1, epithelialmesenchymal transition, hedgehog signaling pathways are important mechanisms affecting HSC proliferation and differentiation [64]. Recent studies found that the TCM compound Diwu Yanggan Capsule is able to inhibit the overexpression of TGF-b1, inhibit the overactivation of hedgehog signaling pathway, prevent the occurrence and development of hepatic fibrosis, and promote liver regeneration and repair by inhibiting the EMT process of HSCs and/ or promoting its MET process [65][66][67].…”
Section: Therapeutic Regulation Of Liver Regeneration By Tcmmentioning
confidence: 99%